A Rare Case of Angina Pectoris with the Longest Ectopic Left Main Coronary Artery Arising from Right Sinus of Valsalva and a Prepulmonic Course. (15th January 2017) - Sinha, Santosh Kumar; Mishra, Vikas; Abdali, Nasar; Singh, Karandeep; Jha, Mukesh Jitendra; Kumar, Ashutosh
Abstract : Knowledge of the morphoanatomical characteristics of the main trunk of the left coronary artery as well as its variations is cornerstone of hemodynamic, correct interpretation of coronary angiogram and for revascularization purpose. The left main coronary artery (LMCA) ranges from 3 to 6 mm in diameter and may be up to 10 to 15 mm in length in humans. We here report a case of the longest anomalous LMCA (56 mm) reported so far in a 35-year-old man with chronic stable angina arising from right sinus of valsalva as seen on conventional angiogram and multidetector computerized tomogram (MDCT).